EFEKTIFITAS PENYULUHAN MEDIA LEAFLET DAN METODE CERAMAH TERHADAP PENGETAHUAN DAN SIKAP SISWI TENTANG PERNIKAHAN DINI DI SMA NEGERI 1 PANCUR BATU DELI SERDANG TAHUN 2019 - efi afrida yanti; yusrawati Hasibuan; Ardiana Batubara; yusniar siregar (COLOSTRUM : Jurnal Kebidanan, 2020)
Introduction: The Council Foreign Relations (CFR) study states that the phenomenon of child marriage is found in many parts of the world. Indonesia is one of the countries with the highest percentage of child marriages in the world (rank 37) and the second highest in ASEAN after Cambodia (WHO 2016). Methods: This type of research used quantitative research methods used are quasi-experimental (quasi-experimental) with pretest-posttest two group design. This study aims to determine how the effectiveness of media counseling, leaflets and lecture methods against student knowledge and attitudes about early marriage at SMA Negeri 1 Pancur Batu. This research was conducted in SMA Negeri 1 Pancur Batu with a population of 124 students with a sample of 55 students. Results and Discussion: The results of the study found that the average knowledge of students about early marriage before being given health education with leaflet media was (21.4%) and after being given health education was (28.6%). While the results of the lecture method can be obtained that the average knowledge of students about early marriage before being given health education was (3.6%) and after being given health education by the lecture method was (89.3%). Conclusion:.The conclusion of this research was that the Lecture Method is more effective in increasing students' knowledge and attitudes about early marriage compared to the media leaflets.